IFPRI's capacity-strengthening strategy - International Food Policy Research Institute (International Food Policy Research Institute, 2009)
The vision of the International Food Policy Research Institute (IFPRI) is a world free of hunger and malnutrition. Capacity strengthening is vital to realizing this vision. Capacity development contributes to agricultural growth, poverty reduction, and economic development. Together with communications, capacity strengthening ensures that IFPRI’s research results have impact on the ground.